The Influencing Factors of The Changing Profession of Coconut Farmers to Service Sector Workers in Pakuweru Village Tenga Subdistric - Iskandar Zulkarnain; Pangemananan Handrie Dunand (CV. Green Publisher Indonesia, 2021)
Background: The total area of the village is 600 hectares and the largest part of the land usage is coconut farming which is 497 hectares, while the rest are roads and rivers.Research purposes: The purpose of the study is to determine whether the wage of labors, the term of payment of wages , and the social prestige affect the job shiffting of agricultural workers to servive sector workers.Research methods: The research method used in this research is a quantitative approach. Research results: The result shows that the changing profession from coconut farm workers to the service workers is determined by 3 (three) factors, that are the wage of labors, the term of payment wages, and social prestige. These are proved by a signigicant level ( α)=0.05, with the result obtained in table with dk=98 is 1.984, it means that the regression coefficient is significant between variable x and variable y , where the value of b=0,92, which means that every increase of 100 units will cause the incracement 0,92 of Y.Conclusion: The influence of changing profession of coconut farmers to service workers determined by three factors that are is the wages factor, the term of paymenet wages, and the social prestige. These are proved by the result of significant level (α) + 0,05, result obtained is(α) = 0,05, so the table with dk= 98 is 1.984, this result means that the null hypothesis is rejected. Means that from the calculation between variable X and Y, where the value of b = 0,92, which means that every increase of 100 units will cause the incracement 0,92 of Y. Furthermore the corelation coefficient of 0,86 which is significant, indicates that there is a relationship or linkage between the wage factor , the term of payment wages , and social prestige towards the changing profession of farm workers, as well as in the regression analysis. The square of correlation coeficient (π ) which is the coeficient of determination amounted to 0,73 =73%. This implies that the effect of the jobshifting of farmer workers to service workers can be explained by wage factors, the length of payment day, and and social prestige , amounted to 73%.